ANALISIS YURIDIS TERHADAP ATURAN PENETAPAN TARIF BEA MASUK ALAT KESEHATAN - NIM. A1012211111, HILTON KUSUMA SIAHAAN (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study examines the juridical analysis of import tariff policies on medical devices and their implications for the fulfillment of the public